1998
DOI: 10.1080/00071669889268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age at onset of production, light regime and dietary calcium on performance, eggshell traits, duodenal calbindin and cholecalciferol metabolism

Abstract: 1. Rate of production and shell thickness (ST) decreased, while body weight (BW), egg weight (EW) and percentage breakage increased progressively with age. Shell weight (SW) increased until 8 to 13 months of age and then decreased. 2. Early onset of production resulted in lower BW and EW at the onset of production, and lower pooled averages of BW, EW, SW and ST, as compared with late or medial onset of production. In 4 out of 5 trials, early onset did not result in the production of more eggs during the laying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To avoid dietary calcium deficiency during intense eggshell calcification, the development of medullary bone occurs at the onset of sexual maturity. Large amounts of calcium are stored in the medullary bone and are released into the blood for eggshell formation during the night hours of laying hens’ photoperiod ( Bar et al, 1998 ). Nevertheless, long-term and intense laying behavior will cause osteoporosis simultaneously with poor eggshell quality in the late phase of laying hens ( Hanna, 2019 ).…”
Section: Effects Of the Intestinal Microbiota Of Laying Hens On Egg Q...mentioning
confidence: 99%
“…To avoid dietary calcium deficiency during intense eggshell calcification, the development of medullary bone occurs at the onset of sexual maturity. Large amounts of calcium are stored in the medullary bone and are released into the blood for eggshell formation during the night hours of laying hens’ photoperiod ( Bar et al, 1998 ). Nevertheless, long-term and intense laying behavior will cause osteoporosis simultaneously with poor eggshell quality in the late phase of laying hens ( Hanna, 2019 ).…”
Section: Effects Of the Intestinal Microbiota Of Laying Hens On Egg Q...mentioning
confidence: 99%
“…This can lead to poor microbial balance in GIT and weak shell quality, both of which might be ameliorated by the use of probiotic. Furthermore, the depressing effects of age on egg production and shell quality in the laying hen are well documented (Bar and Hurwitz 1987;Bar et al 1998). It was reported that probiotics have a good impact on egg production rate, settable egg, and hatchability in broiler breeders, between the ages of 22 and 49 weeks, but no beneficial effects were observed on fertility (Bozkurt et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference in the egg shell thickness thus supporting the reports of Mahdavi et al (2005) that addition of lactic acid producing bacteria to the laying hen diet had no significant effect on egg shell thickness. Bare and Striem (1998) stated that a probable explanation for thin egg shell in older hens may be lessening of calcium deposition with the passage of time. Protein and fat retention results obtained disagreed with the report of that similar treatments did not influence nutrient retention.…”
Section: Discussionmentioning
confidence: 99%